Wartime panic attacks in children with special educational needs - O. Vovchenko (Mukachevo State University, 2023)
The study is relevant because it covers the main ways to help during panic attacks in the most vulnerable category of the population of Ukraine, children with special educational needs, in conditions of war and experiencing traumatic events. The purpose of the study is to identify the main methods of psychological assistance during panic attacks in children with special educational needs. The main practice-oriented research methods were observation, conversations, interviews, questionnaires in the process of meetings with children, and the collection of medical history. Based on the results of applying practical research methods, effective, unified step-by-step psychological support for this category of persons was developed. The study describes the main methods of psychological assistance, as the main chosen technique of cognitive behavioural therapy, which should be accompanied by additional communication with parents and teachers to disseminate information, practical skills, and actions in situations of panic attacks in children with special educational needs. The study has an evidence base, is a praxeological writing, and is still being conducted based on educational institutions and rehabilitation centres for children with special educational needs, in particular, those with visual, hearing, intelligence, and speech disorders. The main signs of behaviour and emotional states of children experiencing panic attacks are characterised. It is stated that a panic attack in children with special educational needs occurs from excessive emotional load, exhaustion, traumatic event, stress, and negative dynamics of habitual life. The final result of the study is outlined, namely: the development of a unified protocol of psychological assistance and support for children with special educational needs experiencing panic attacks, their parents, and relatives. At this stage of the study, the results obtained allowed forming effective advice to parents, people who happened to be nearby, and teachers during the onset of a panic attack in a child.